2013
DOI: 10.1155/2013/845916
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Achievable Flow Length in Injection Moulding of Polymeric Materials with Dynamic Mould Tempering

Abstract: A variety of parts in microsystems technology are manufactured by injection moulding of polymeric materials. In Particular the high cooling velocity affects negatively the process and the resulting part properties. The scope of this paper is to investigate the influence on the reachable flow length in injection moulding of different polymeric materials. The results indicate that the mould temperature has less impact on the achievable flow length of the polymer melt as the injection pressure. A higher mould tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Previous approaches have focused on reducing the viscosity of the melt through high melt temperatures or dynamic mold temperature control to such A second example in which unintentionally high-pressure gradients can occur, is micro injection molding. In the production of thin-walled structures in injection molding, flow path and cross-section-dependent pressure and temperature differences can often lead to difficult mold filling, especially during the injection phase [30]. Previous approaches have focused on reducing the viscosity of the melt through high melt temperatures or dynamic mold temperature control to such an extent that the cavity can still be completely filled [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Previous approaches have focused on reducing the viscosity of the melt through high melt temperatures or dynamic mold temperature control to such A second example in which unintentionally high-pressure gradients can occur, is micro injection molding. In the production of thin-walled structures in injection molding, flow path and cross-section-dependent pressure and temperature differences can often lead to difficult mold filling, especially during the injection phase [30]. Previous approaches have focused on reducing the viscosity of the melt through high melt temperatures or dynamic mold temperature control to such an extent that the cavity can still be completely filled [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that ATT optimized not only the rheological characteristics of the process but also the morphology, and hence the overall properties of the molded parts, without increasing the cycle time. Meister and Drummer investigated the influence of mold temperature of the flow length of a spiral shaped mold, for which the cross‐section of the spiral had a dimension of 0.3 × 1.5 mm. The variotherm temperature control system used water as the circulating fluid and had a heating and a cooling circuit‐switching device and allowed a fluid temperature of up to 200°C.…”
Section: Various Heating Methods For Variotherm Processmentioning
confidence: 99%
“…The influence of process parameters was also investigated in publications [7][8][9]. And finally, following published papers [10][11][12] investigated various effects of process parameters, for example pressure and melt flow index, or the reason for the creation of flow marks.…”
Section: Introductionmentioning
confidence: 99%